Upaya Meningkatkan Kemampuan Motorik Halus Anak Usia 4-5 Tahun Melalui Kegiatan Cooking Class Di TK Dwi Karya Tanjung Koto Kampar Hulu - Tri Wahyuni; Yenda Puspita; Musnar Indra Daulay; Moh. Fauziddin; Joni Joni (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to improve the fine motor skills of children aged 4–5 years through cooking class activities at TK Dwi Karya Tanjung Koto Kampar Hulu. This research is a classroom action research (CAR) conducted in two cycles, each consisting of two meetings. The subjects of the study were 15 children in group B1. Data collection methods included observation, documentation, and interviews. Data analysis techniques were carried out using both qualitative descriptive and quantitative approaches. The results showed an improvement in children’s fine motor skills after participating in the cooking class activities. In the pre-action phase, most children were still in the "not yet developed" category. However, after the first and second cycles, there was a significant increase in indicators such as grasping, stirring, shaping, and wrapping dough. The cooking class proved effective in providing enjoyable and meaningful stimulation for the development of children's fine motor skills. Thus, this activity can be considered an innovative alternative learning method for early childhood education